Qualidade de vida: inter-relações do tempo livre para os colaboradores de uma multinacional do ramo de alimentos - Rugiski, Marcelo (2007)
This research was carried out at a multinational industry in the food branch and had as objective to identify the collaborators’ perception concerning their Quality Of Life and its inter-relation with free time. It is an applied research with an approach predominantly qualitative. Due to its objectives, the research is descriptive, using a case study as the procedure method. The data collection was carried out through two instruments. The first one was a questionnaire elaborated by the World Health Organization on Quality Of Life, the WHOQOL-100, and the second was a semistructured interview composed by six questions. The sample design was formed by stratification. The Quality of Life was evaluated through the WHOQOL-100, which is composed by six domains: Physical, Psychological, Level of Independence, Social Relationships, Environment and Spirituality/Religion/Personal Beliefs. The analysis of score components of WHOQOL-100 revealed that the perception concerning the collaborators’ Quality of Life presents an intermediate position of satisfaction, with a 69,22% score. It might be said that this result may be a consequence of unsatisfaction inherently human in the search of QOL. From the data obtained it might be identified that the domain Level of Independency received the highest level among the others, with 79,47%, followed by Spirituality/Religion/Personal Beliefs with 78,98%, Social Relationships (74,98%), Psychological (69,86%), Environment (61,26%) and Physical with 60,36%, that obtained the lowest score. The facet Quality of Life from the evaluated person’s point of view obtained a percentile of 69,22%. The factors that positively contributed in the evaluation of LOQ of the group researched by the WHOQOL-100 questionnaire may be represented by the facets that obtained satisfactory evaluation, that is, scores above 75% average, which are: Self esteem, body image, mobility, dependency on medication and treatments, personal relations, sexual activity, Spiritual/Religious/Personal Beliefs aspects and Work Capacity. Concerning the factors that negatively contribute to the QOL of the researched group, the results from WHOQOL-100 indicate four facets pertaining to the domain Environment, and they are: Physical Ambient (pollution/noise/traffic/weather), Participation in and opportunities of recreational activities/leisure, Financial Resources and Physical Safety, and Protection. These facets obtained the lowest average regarding satisfaction, ranging from 55,11% to 50,44%. Among the facets that had lower averages for this research, it was attempted to deepen and develop a more accurate discussion on Participation and Opportunities of recreational activities/leisure, more specifically on leisure. For that matter, an interview was developed for a better perception of reality presented in activities of free time, as well as to investigate which common activities of leisure are usually developed by this group. It was possible to verify that, during the free time of the referred workers, there is a predominance of routinely activities little pleasant in relation to the typical leisure activities, and that the researched company may interfere positively in QOL of it collaborators through actions that enable them to access leisure activities.